Revised taxonomy and nomenclature of rodent Pasteurellaceae: Implications for monitoring. (June 2018) - Boot, R; Nicklas, W; Christensen, H
Pasteurellosis is a well-recognized disease with similar pathology in all laboratory rodent species. Pasteurella pneumotropica is the most frequently mentioned member of the Pasteurellaceae isolated from mice and rats. Numerous other Pasteurellaceae taxa have been obtained from mice, rats, and other rodent species. Recently, rodent Pasteurellaceae have been submitted to comprehensive genetic and phenotypic (polyphasic) taxonomic studies. As a result they are now classed within six validly published new genera, namely Cricetibacter, Mesocricetibacter, Mannheimia, Muribacter, Necropsobacter, and Rodentibacter. All previously used names such as P. pneumotropica have become obsolete. The new classification forms a firm basis for the correct phenotypic identification of Pasteurellaceae from laboratory animals and for the selection of strains for pathogenicity studies. Consequences of taxonomic changes notably involve molecular methods used for the detection of Pasteurellaceae infection in laboratory animal colonies. Testing may be done using primer sets that detect all Pasteurellaceae taxa or sets developed to detect host-specific members of the family.